2017
DOI: 10.1080/17483107.2017.1413145
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction and perceptions of long-term manual wheelchair users with a spinal cord injury upon completion of a locomotor training program with an overground robotic exoskeleton

Abstract: This study provides new insights on satisfaction and perceptions of wheelchair users while also confirming the relevance to continue to improve such technologies, and informing the development of future clinical trials. Implications for Rehabilitation All long-term manual wheelchair users with a spinal cord injury who participated in the study are unanimously satisfied upon completion of a 6-8-week locomotor training program with the robotic exoskeleton and would recommend the program to their peers. All long-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 28 publications
4
54
0
Order By: Relevance
“…Further large clinical trials with sufficient rehabilitation durations, as well as adequately powered homogenous studies, are required to better understand these effects of RLT on individuals with SCI. and had tendencies towards strong positive comments regarding the acceptability and emotional/health benefits of the training process (11,15,16,18,19,(25)(26)(27). Improvements in QoL and psycho-emotional wellness were also reported post-intervention (7,25).…”
Section: User-satisfactionmentioning
confidence: 96%
See 1 more Smart Citation
“…Further large clinical trials with sufficient rehabilitation durations, as well as adequately powered homogenous studies, are required to better understand these effects of RLT on individuals with SCI. and had tendencies towards strong positive comments regarding the acceptability and emotional/health benefits of the training process (11,15,16,18,19,(25)(26)(27). Improvements in QoL and psycho-emotional wellness were also reported post-intervention (7,25).…”
Section: User-satisfactionmentioning
confidence: 96%
“…Stampacchia et al (26) found that participants rated the positive sensations with high scores (mean VAS score 6) and the negative experiences with low scores (mean VAS score 2.5). Gagnon et al (27) used a VAS of 0-100%, in which the mean percentages for each question indicated that participants were satisfied with the training (mean score 95.7%), felt motivated to continue training (91.3%), and that there was strong ability to use the device (79.6%). A mean score of 67.9% was given for the perceived health benefits and 16.7% for complications and risks of using the device (27).…”
Section: Ambulatory Outcomesmentioning
confidence: 99%
“…We hypothesized that patients would present difficulties falling asleep and/or staying asleep, would more often wake up during the night, have shorter sleep duration, and report more daytime sleepiness as compared to ablebodied. Wheelchair users with a SCI, who underwent a locomotor training program, perceived improvements in their sleep quality [13], whereas regular physical activity contributed to a better pain control, improvements in their overall health status and life satisfaction in this population [14][15][16][17]. Actigraphy is considered a suitable method of measuring physical activity in people with SCI and has concurrent validity with a self-report measure of activity intensity and frequency in wheelchair users [18].…”
Section: Introductionmentioning
confidence: 99%
“…Regular use of robotic exoskeletons may help limit secondary conditions following SCI, including pain, spasticity, and decreased bone mineral density [ 9 – 11 ]; In addition, healthcare providers and home users acknowledge the psychological benefits that exoskeletons provide through eye-level social interactions and increased confidence [ 12 , 13 ]. Therapists’ use of these devices is still in its infancy relative to user screening, therapy time, and dosage [ 14 17 ]. Studies describe user discomfort, lack of fall mitigation features, and limited utility as major design limitations [ 18 ].…”
Section: Introductionmentioning
confidence: 99%